Numerical simulation of particles movement in cellular flows under the influence of magnetic forces - Hribersek, Matjaz; Steinmann, Paul; Ravnik, Jure; Vogel, Franziska Anna (Proceedings of the 82nd Annual Meeting of the International Association of Applied Mathematics and Mechanics, 2011)
A numerical model of particle motion in fluid flow under the influence of hydrodynamic and magnetic forces is presented. As computational tool, a flow  solver based on the Boundary Element Method is used. The Euler-Lagrange  formulation of multiphase flow is considered. In the case of a particle with a magnetic moment in a nonuniform external magnetic field, the Kelvin body force  acts on a single particle. The derived Lagrangian particle tracking algorithm is  used for simulation of dilute suspensions of particles in viscous flows taking into account gravity, buoyancy, drag, pressure gradient, added mass and magnetophoretic force. As a benchmark test case the magnetite particle motion in  cellular flow field of water is computed with and without the action of the magnetic  force. The effect of the Kelvin force on particle motion and separation from themain flow is studied for a predefined magnetic field and different values of  magnetic flux density.
UnivIS-Import:2015-04-16:Pub.2011.tech.FT.FT-TM.numeri_5